Cellular senescence in age-related cardiovascular disease: past and future - Wu, Xiang; Zhou, Qingyu; Huang, Yingying; Jiang, Wangqing; Zhou, Jianming; Qian, Ke; Pan, Yinchen; Wu, Zuyao; Zhang, Jingjun; Aimaiti, Madinai; Zhou, Qi; Lv, Feizhou; et al. (Frontiers in Aging, 2026)
Cellular senescence is a distinct and definable biological state characterized by irreversible cell cycle arrest, accompanied by the activation of the DNA damage response (DDR), telomere shortening, the senescence-associated secretory phenotype (SASP), and metabolic dysfunction. While senescent cells represent only a small fraction of the total cell population in tissues, they exert a disproportionate and systemic impact on age-related cardiovascular disease (CVD) through paracrine and endocrine mechanisms. This review moves beyond a descriptive list of pathways and instead proposes a unified framework centered on how a small number of senescent cells can reprogram the cardiovascular microenvironment. We focus on the SASP as the central executor of this systemic effect, disseminating local senescence and driving chronic inflammation, fibrosis, and dysfunction across major cardiovascular cell types (cardiomyocytes, endothelial cells, fibroblasts, smooth muscle cells). We integrate key regulatory networks such as mTOR, AMPK, and Sirtuins that modulate the SASP and the senescent state. Furthermore, we discuss the translational promise of senolytics (agents that clear senescent cells) and senomorphics (agents that suppress the SASP) as novel strategies for delaying cardiovascular aging and treating age-related CVD, providing a forward-looking perspective on targeting senescence to promote cardiovascular health. Current research challenges include mechanistic complexity and limitations of animal models and in vitro systems. In the future, it is necessary to combine single-cell sequencing, metabolic intervention, and interdisciplinary technologies to analyze the heterogeneity of cellular aging, and develop early warning and precision treatment strategies based on aging biomarkers, so as to provide new ideas for delaying cardiovascular aging.